Experiences of discrimination among youth with HIV/AIDS in Ibadan, Nigeria - Adesola O. Sangowawa; Eme T. Owoaje (AOSIS, 2012)
Nigerian youth currently bear a disproportionate burden of the HIV epidemic. This paper presents findings on the occurrence of HIVrelated discrimination among youth with HIV accessing care in Ibadan, Nigeria. A cross-sectional study was conducted and information on history of discrimination experienced by 170 youth with HIV was obtained. About 80% of respondents had disclosed their HIV status. The majority had informed their spouses (66.3%), mothers (47.1%), fathers (39.1%) and siblings (37.7%). Sixteen (11.5%) respondents [15 (93.8%) females and one (6.2%) male] had suffered discrimination since disclosure of their status. Of these, 25.0% respondents were sent out of their matrimonial homes by their husbands, 25.0% were abandoned by their spouses and 12.5% indicated their fiancé broke up their relationship. A higher proportion of females (12.9%) than males (4.3%) had suffered discrimination. In addition, a significant proportion of respondents who were separated/divorced (73.3%) had been victims of discrimination compared with those who were widowed (10.5%) or single (5.9%) (P<0.05). The study confirmed that young people living with HIV/AIDS, especially women experience extreme forms of discrimination. More efforts aimed at addressing HIV/AIDS-related discrimination are required especially as it is a known barrier to HIV prevention and treatment efforts.